Effect of high-intensity sonication on the dispersion of carbon-based nanofilaments in cementitious composites, and its impact on mechanical performance. (15th December 2017) - Alrekabi, S.; Cundy, A.B.; Lampropoulos, A.; Whitby, Raymond L.D.; Savina, I.
Highlights: High-intensity sonication improved the dispersion and reinforcing effects of carbon-based nanofilaments in cement composites Addition of only 0.025% nanofilaments by weight of cement generated significant improvements in material performance Increases in compressive strength of 24-32%, tensile strength of 45-50%, and flexural toughness of 30-40%, were observed Short-period sonication can produce desired dispersion levels for manufacture of structurally-enhanced cementitious materials Graphical abstract: Abstract: Carbon-based nanofilaments are promising materials for improving the mechanical performance of cementitious composites. To date, the main challenge in their effective use has been controlling the dispersion of these additives in water and in the resulting mixed composites due to their strong van der Waals self-attraction and hydrophobic surfaces. This study uses high-intensity sonication to disperse different nanofilament types in water, and assesses their resulting reinforcing efficiency in cementitious composites. The proportion of nanofilaments used (in this case, multiwall carbon nanotubes MWCNTs, functionalized multiwall carbon nanotubes F-MWCNTs, and carbon nanofibres CNFs) was 0.025% by weight of cement. Aqueous dispersions were examined using transmission electron microscopy (TEM) and optical microscopy, and ultraviolet-visible (UV–vis) spectroscopy. Compressive, flexural and splitting tensile strengths tests, and porosity and density measurements, were used to evaluate the mechanical properties of the composites. High-intensity sonication over short durations significantly improved the dispersion, and reinforcing and filling effects, of carbon-based nanofilaments in cementitious composites, with increases in compressive strength of 24–32%, splitting tensile strength of 45–50%, and flexural toughness factor of 30–40%, observed after 28 days curing. A 17–26% reduction in the porosity of the composite materials was also recorded.